Contracts Relating to Marriage: Part II - Sinnadurai, Visu (Journal of Malaysian and Comparative Law, 1980)
Part I of this paper dealth with marraige brocage agreements. In this part of the paper, two other aspects of agreements relating to marriage will be considered: agreements in restraint of marriage and agreements made by married persons to marry another person. As pointed out earlier, the common feature of the agreement under study is that they are rendered void under the common law as being opposed to public policy.